Calculating and analysis of water piping system from Timah Tasoh to Kuala Perlis - Chong, Tong San
This final year project is about calculating and analysis of water piping system from Timah Tasoh to Kuala Perlis water tower to make sure the enough need of water for Kuala Perlis residents.